Running for Korea: Rethinking of sport migration and in/flexible citizenship - Choi, N. (International Review for the Sociology of Sport, 2018)
Human migration is one of the defining features of a transnational age. Challenging the conventional knowledge that identity and citizenship are connected to one territorial state, both migrant and repositioned subjects create a new understanding of identity, belonging, and citizenship within multiple transnational connectivities. Sport particularly produces a new version of belonging referred to as flexible citizenship, including various kinds of skilled workers crossing national borders. In the process of migration, governments play a crucial and a decisive role by determining permission via specific legislation enactment; South Korea`s immigration policy, Special Naturalization, is a notable example. Despite the legally encouraged mobility that favors flexible citizenship by state power, this repositioning is regulated and limited by the intricate socio-political logics of race, class, and national identity. Focusing on the controversial issues of the Kenyan-born marathoner Wilson Loyanae Erupe and his bid for Korean citizenship, this study critically examines the tensions surrounding sport migration, flexible citizenship, race, and nationalism. Drawing on the theoretical ideas of critical race studies, specifically, it queries the conflicting encounters of transnational migration and being a Korean citizen to illuminate the structures of racial domination in Korea often seen as a racially and ethnically homogeneous society.